COMPARATIVE ANALYSIS BETWEEN PALMAR PRESSURE FORCE AND ITS RELATION TO BODY MASS AND BALANCE INDEX IN ELDERLY - Alves, Letícia Prado; Rodrigues, Maynne Karolline Barcelos; Veneziano, Leonardo Squinello Nogueira; Silva, Renata do Nascimento; Pacheco, Leanny Rosa; Silva, Renato Canevari Dutra da; Cabral, Rejane Maria Cruvinel (International Journal of Movement Science and Rehabilitation, 2020)
Through the assessment of the Palmar Grip Strength (FPP) it is possible to calculate the individual’s muscle strength index, and with the help of the BMI calculation can assess if the individual is overweight. Time up and Go (TUG) testing is done to assess balance and risk of falls. Objective: To verify muscle strength and its relationship with BMI and balance and risk of falls in elderly women. 40 elderly women were evaluated, 20 sedentary and 20 active women selected at the academy school of the University of Rio Verde. Bilateral FPP, BMI for body composition and TUG were evaluated to assess balance. Descriptive analysis of the results was performed to calculate the mean and standard deviation. The right side PPF in sedentary volunteers presented average of 13.75 Â± 10.14 Kgf and in active 17.40 Â± 10.54 Kgf, an increase of 26.54% for active ones. On the left side sedentary volunteers had an average of 11,40 Â± 7.50 Kgf, and in the active ones 15.05 Â± 10.68 Kgf, presenting an increase of 36.32% for the active ones. BMI (kg/m2) values in sedentary volunteers were: average of 25.77 Â± 43.38 and in active volunteers 28.28 Â± 47.38. In the TUG test, there was a 35.74% reduction in the test time. It presented mean of 19.92 Â± 7,97 s for sedentary and 12.80 Â± 4,69 s in active elderly. PPF is directly linked to the level of physical activity and lower BMI and better balance.